Penggunaan Kappa Caragenan Sebagai Bahan Pengenkapsulasi Lactobacillus acidophilus Terhadap Viabilitas dan â€œShelflifeâ€ - Setijawati, Dwi; Firdaus, Muhammad (JFMR (Journal of Fisheries and Marine Research), 2019)
The aim of the study was to find out the effect of using kappa caragenan as an Lactobacillus acidophilus encapsulating material on viability and â€œshelflifeâ€. The research method was an experimental laboratory design with Completely Randomized Design (CRD), ANOVA, followed by the Fisher test, to test for differences. Data analysis using Minitab 16 software. The research treatment was the concentration of kappa caragenan with sub-treatment as follows: A1 (2%); A2 (2.5%); A3 (3.0%); A4 (3.5%); A5 (4.0%); A6 (4.5%) The results showed that the use of different concentrations of kappa caragenan as an encapsulation material for Lactobacillus acidophilus had a very significant Â difference effect on the viability of Lactobacillus acidophilus and encapsulation yield. Viability increases with increasing concentration of kappa caragenan used. The highest viability of 8.71 log CFu / mL was obtained using a 4.5% kappa caragenan concentration with a â€œShelflifeâ€ calculation of 65.73 years of storage at 5oC. The research suggestion was testing 4.5% Lactobacillus acidophilus microcapsules encapsulated by kappa carrageenan in GI Tract simulation solution.Â Keywords: Eucheuma cottonii, Microencapsulation, Emulsification